Becoming - Reynolds, Kimberly M (Centre for Film and Media Studies, 2021)
This thesis project accompanies the 2019 photographic portraiture series entitled Becoming. Using James Baldwin, Audre Lorde and Zora Neale Hurston as departure points, both the photo series and this academic explanative seeks to explore the question of what does it mean to become? Or in other words, what is the imperative to be who you are, to actualize within a space that demonstrates a regular investment in the destruction of bodies that are Black and queer. Through a set of five individual interviews, the questions of what does it mean to be who you are? why is it important? how do you become through your creative work? serve to create space for knowledge production, combatting what Spivak dubs as epistemic violence. Guided by the principles of post colonial life writing, African and Black feminist thought, Black queer theory, and art as an emancipatory tool, this thesis centers voices often theorized about yet rarely heard and argues that creative work more broadly offers a path for liberation. The published work of Becoming, both the photographs and interviews, can be found at http://www.becomingphotoseries.com/ and fulfils the creative media aspect of this dissertation/creative project.